The Human Endolymphatic Sac and Inner Ear Immunity: Macrophage Interaction and Molecular Expression - Kämpfe Nordström, Charlotta; Danckwardt-Lillieström, Niklas; Laurell, Göran; Liu, Wei; Rask-Andersen, Helge (Frontiers in Immunology, 2019)
Background: The endolymphatic sac (ES) is endowed with a multitude of white blood cells that may trap and process antigens that reach the inner ear from nearby infection-prone areas, thus serving as an immunologic defense organ. The human ES—and, unexpectedly, the rest of the inner ear—has recently been shown to contain numerous resident macrophages. In this paper, we describe ES macrophages using super-resolution structured fluorescence microscopy (SR-SIM) and speculate on these macrophages’ roles in human inner ear defense. Material and Methods: After ethical permission was obtained, human vestibular aqueducts were collected during trans-labyrinthine surgery for acoustic neuroma removal. Tissues were placed in fixative before being decalcified, rapidly frozen, and cryostat sectioned. Antibodies against IBA1, fractalkine (CX3CL1), toll-like receptor 4 (TLR4), class of differentiation 68 (CD68), CD11b, CD4, CD8, and the major histocompatibility complex type II (MHCII) were used for immunohistochemistry. Results: A large number of IBA1-positive cells with different morphologies were found to reside in the ES; the cells populated surrounding connective tissue and the epithelium. Macrophages interacted with other cells, showed migrant behavior, and expressed immune cell markers, all of which suggest their active role in inner ear immune defense. Discussion: Based on the study’s findings, we conjecture that the human ES enhances inner ear immune protection by strategic “off-site” antigen processing, thus avoiding the induction of pro-inflammatory cytokines and antimicrobial activity near the vulnerable inner ear receptors.